2021
DOI: 10.1122/8.0000289
|View full text |Cite
|
Sign up to set email alerts
|

Particle contact dynamics as the origin for noninteger power expansion rheology in attractive suspension networks

Abstract: In medium amplitude oscillatory shear (MAOS), the cubic scaling of the leading order nonlinear shear stress (σ3 ∼ γ m 3 0 , m3 = 3) is the typical expectation. Expanding on the work by Natalia et al. [J. Rheol., 64(3): 625 (2020)], we report non-cubical, non-integer power law scalings m3 for particle suspensions in two immiscible fluids with a capillary attractive interaction, known as capillary suspensions. Here, we show that distinct power law exponents are found for the storage and loss moduli and these non… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 59 publications
1
4
1
Order By: Relevance
“…The results of the power law fitting of σ ′ 3 and σ ′′ 3 for both the samples with ϕ sec = 1 vol% and adjusted secondary fluid can be seen in Figure 6. First, both the scaling of m 3,elastic and m 3,viscous is noncubic and noninteger for all samples, in accordance with the works of Natalia et al [43,42] The power law exponents do not differ significantly between sample groups, with m 3,elastic values falling mostly between 1.5 and 2.5 and m 3,viscous values between 1 and 2. The spread on the data is quite large due to the limited number of datapoints above the noise floor available for the fitting owing to the 8 mm parallel plate geometry.…”
Section: Medium Amplitude Oscillatory Shear To Investigate Particle C...supporting
confidence: 89%
See 4 more Smart Citations
“…The results of the power law fitting of σ ′ 3 and σ ′′ 3 for both the samples with ϕ sec = 1 vol% and adjusted secondary fluid can be seen in Figure 6. First, both the scaling of m 3,elastic and m 3,viscous is noncubic and noninteger for all samples, in accordance with the works of Natalia et al [43,42] The power law exponents do not differ significantly between sample groups, with m 3,elastic values falling mostly between 1.5 and 2.5 and m 3,viscous values between 1 and 2. The spread on the data is quite large due to the limited number of datapoints above the noise floor available for the fitting owing to the 8 mm parallel plate geometry.…”
Section: Medium Amplitude Oscillatory Shear To Investigate Particle C...supporting
confidence: 89%
“…If the region in between the G ′′ maximum and the crossover point is included as well, this relaxes the scaling of m 3,elastic to values between 1.5 and 1, which is more similar to the pendular capillary suspension system in the work of Natalia et al [42] Important to note is that the scaling that can be observed is limited by the sensitivity window of the rheometer, shown as gray shading in Figure 5. As a result of the smaller parallel plate geometry, the noise floor corresponding to the sensitivity limit of the rheometer is shifted to higher stress values, which could mask an initial cubic scaling, as already discussed by Natalia et al [42] For the interval shown in Figure 5, the elastic and viscous exponents are 1.7 ± 0.1 and 1.6 ± 0.2 using the 8 mm. The dashed lines show the effect on the fit after including or excluding an extra datapoint.…”
Section: Medium Amplitude Oscillatory Shear To Investigate Particle C...mentioning
confidence: 65%
See 3 more Smart Citations